Analisis Peran Pendidikan Agama Islam dalam Pembentukan Karakter Religius Siswa Kelas V MI Darul Ulum Ngaliyan - Novita, Catrin Erma; Ardani, Alvina Verda; Andriyani, Rossa; Nugraheni, Shyabila Ivenne Liselya; Kiptiyah, Siti Maryatul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Character education is a process of instilling positive values in students to build good character. The aim of this research is to analyze the role of Islamic Religious Education in forming students' religious character. Teachers and 32 class V students of MI Darul Ulum Ngaliyan were used as research subjects. Observation, interviews, questionnaires and documentation are the instruments and methods used in this research. Based on the results of research conducted at MI Darul Ulum Ngaliyan, the role of Islamic religious education in forming students' religious character is very important. The process of learning Islamic principles as the basis of religious character is the key to forming a strong moral foundation in students. Methods of getting used to routine religious activities such as midday prayers, noon prayers, Juz 'Amma activities, reading the Asmaul Husna, and PHBI activities also have a positive impact on the formation of students' religious character. Through familiarization with religious activities, it is hoped that students will become accustomed to commendable, disciplined and responsible behavior. Thus, the formation of students' religious character at MI Darul Ulum Ngaliyan can be carried out well through the role of Islamic religious education and methods of getting used to routine religious activities